ANALISIS GAYA BELAJAR SISWA YANG AKTIF DALAM PEMBELAJARAN SOSIOLOGI DI KELAS XI IIS 1 - Clara Valentina; Yohanes Bahari; Imran Imran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe title of this thesis is "Analysis of Active Learning Styles of Students in Sociology Learning in Class XI of IIS 1 SMA KemalaBhayangkari". The problems of this research are (1) how, and (2) the factors which effect type of student’s learning style which is active in learning sociology. The purpose of this research to know about those problems about the researcher used kualitatif method which descriptive research and the participants of this research are six students of class XI IIS 1. The tools that used to collect the data are observation, interview and documentation. The result of this research are (type of students learning style are visual, auditorial, and kinestik). The students that used visual and auditorial learning style are MT and VI, but they more dominan to used visual. The students that used visual, auditorial, kinestik are AD, DS, RS and UN, but they more dominan to used auditorial learning style. (2) they are two factors which effect the students learning style are physical (health and disability) and psychological (about the relationship between the students and the people around them).Keywords:Active Learning, Learning Sociology Learning Style